Enhanced Amikacin Diffusion With Ultrasound and Microbubbles in a Mechanically Ventilated Condensed Lung Rabbit Model - Espitalier, Fabien; Darrouzain, François; Escoffre, Jean-Michel; Ternant, David; Piver, Eric; Bouakaz, Ayache; Remerand, Francis (Frontiers in Pharmacology, 2020)
The poor diffusion of intravenous antibiotics in lung tissue makes nosocomial pneumonia challenging to treat, notably in critical patients under mechanical ventilation. The combination of ultrasound and microbubbles (USMB) is an emerging method for non-invasive and targeted enhancement of uptake of various drugs in several organs. This study aims to evaluate if USMB may increase amikacin concentration in condensed lung tissues in a mechanically ventilated rabbit model. When applied 60 minutes or 160 minutes after the beginning of an intravenous amikacin infusion, USMB increased amikacin concentration in the condensed lung tissue by 1.33 (p=0.025) or 1.56-fold (p=0.028) respectively. When applied 70 minutes after the beginning of an intravenous amikacin infusion, USMB increased amikacin concentration in the muscle tissue by 2.52 (p=0.025). In conclusion, this study demonstrates that USMB is a promising method for the targeted delivery of amikacin in mechanically ventilated condensed lung, thus opening new therapeutic fields against lung infections.